ANXIETY AND DEPRESSION AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS USING THE VALIDATED FILIPINO VERSION OF THE HOSPITAL ANXIETY AND DEPRESSION SCALE - Nolasco, Marjorie; de Guzman, Adrian Joseph; Faustino, Collene Marizza; Sampana, Allanbert; Medina, Ma. Adelita (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION In 2017, over 3.7 million Filipinos have diabetes according to the International Diabetes Federation. Similarly, 3.29 million Filipinos are battling depression and 3.07 million are living with anxiety. Studies have concluded that anxiety and depression are burdensome comorbidities in people with T2DM. Clinicians should be aware that even subclinical symptoms of depression may negatively impact diabetes self-care behaviors. We therefore conducted this study to determine the prevalence of anxiety and depression in patients with diabetes. METHODOLOGY This was a cross-sectional single-center study using nonprobability sampling conducted on September 2018 at the OPD. All patients diagnosed with T2DM, age 35 years and above, currently receiving glucose-lowering medications were included in the study. A self-administered questionnaire was used to obtain the sociodemographic and clinical characteristics of the participants. HADS-P was used to screen for anxiety and depression. The relationship between the clinical variables and anxiety and depression was assessed by performing chi-square and Fisher’s Exact test. RESULTS A total of 63 patients were included in the analysis. Anxiety was seen in 26 (41%) patients and 10 (16%) patients were found to have symptoms of depression. Significant association was found between monthly income and anxiety (p=0.040 <0.05). There was significant association between depression, civil status (p=047 0.05), and monthly income (p=0.049 <0.05). CONCLUSION Mood disorders could be readily observed among patients with T2DM. Younger patients were more likely to suffer from depression. Other factors such as low income, poor moral and social support especially among married and widowed/er individuals are identified.